Molecular beam study of the NO plus CO reaction on Pd(111) surfaces - Thirunavukkarasu, K; Thirumoorthy, K; Libuda, J; Gopinath, Chinnakonda S. (Journal of Physical Chemistry B, 2005)
Nitric oxide (NO) reduction with carbon monoxide (CO) on the Pd(111) surface was studied under isothermal conditions by molecular beam techniques as a function of temperature, NO:CO beam composition, and beam flux. Systematic experiments were performed under transient and steady state conditions. Displacement of adsorbed CO by NO in the transient state of the reaction was observed at temperatures between 375 and 475 K for all the NO: CO compositions studied. NO accumulation occurs on Pd(l 11) surface under steady state conditions, below 475 K, due to stronger chemisorption of NO. The steady state reaction rates attain a maximum at about 475 K, nearly independent of beam composition. N-2 was found to be the major product of the reduction, along with a minor production of N2O. The production of N2 and N2O indicates molecular and dissociative adsorption of NO on Pd(l 11) at temperatures up to 525 K. Postreaction TPD measurements were performed in order to determine the nitrogen coverage under steady-state conditions. Finally, the results are discussed with respect to the rate-controlling character of the different elementary steps of the reaction system.